Commitment dynamics of novice teachers in training and understanding of identity processes - Serres, Guillaume; Perrin, Nicolas; Leblanc, Serge; Ria, Luc (Swiss Journal of Educational Research, 2018)
In reference to the challenges of this special issue, the paper gives an account for learning experiences of beginning teachers and of the changes in their commitment identifiable in the process. The approach based on longitudinal studies places particular importance on the dynamic dimension of phenomena over the training period. Three modes of changing and reconfigurating the novice teachers’ commitment were identified: «finding a way out», «transitising» and «massively reconstructing». A better understanding of identity processes involved in these reconfigurations seems likely to open promising avenues for training.